(untitled) (Journal of Hama University, 2025)
The main objective of this research is to clarify how to employ weight limits in robust Optimization of stock portfolios listed in the Damascus Stock Exchange, by clarifying the concept of robust Optimization and how to use them in the field of selecting the components of the optimal investment portfolio, and then determining the inputs necessary to select the components of the optimal stock portfolio using weight limits and clarifying how to estimate them and clarify the amounts of expected return and the degree of risk associated with the portfolio formed using weight limits, and thus determining the extent of the effectiveness of employing these limits in selecting the components of the optimal stock portfolio. The application was carried out on a sample of 26 shares of companies listed on the Damascus Stock Exchange during the period (1-1-2020 to 23-6-2024) and using the Microsoft Office Excel 2013 spreadsheet program in the process of Optimization and comparing the outputs within the framework of several scenarios. The study reached a set of results, the most prominent of which is that using weight limits when choosing the components of the optimal stock portfolio helps the investor in the Damascus Stock Exchange to form portfolios that are consistent with his goals in terms of the desire to maximize returns or reduce risk, according to the mathematical program formulated by him and aimed at choosing the optimal formation of the portfolio, taking into account the primary goal of the investor when formulating the objective function, which is either the degree of risk required to be reduced or the expected return required to be maximized. The resulting portfolios are highly diversified portfolios due to their distribution of capital among all stocks nominated for investment, with the largest part of it concentrated in stocks with the characteristics desired by the investor, whether in terms of return or risk.